Model transfer from 2D to 3D study for boxing pose estimation - Lin, Jianchu; Xie, Xiaolong; Wu, Wangping; Xu, Shengpeng; Liu, Chunyan; Hudoyberdi, Toshboev; Chen, Xiaobing (Frontiers in Neurorobotics, 2023)
The boxing sport is walking into the Chinese campus, resulting in a coaching shortage. The human pose estimation technology can be employed to estimate boxing poses and teach interns to relieve the shortage. Currently, 3D cameras can provide more depth information than 2D cameras. It can potentially improve the estimation. However, the input channels are inconsistent between 2D and 3D images, and there is a lacking of detailed analysis about the key point location, which indicates the network design for improving the human pose estimation technology. Therefore, a model transfer with channel patching was implemented to solve the channel inconsistent problems. The differences among the key points were analyzed. Three popular and highly structured 2D models of OpenPose (OP), stacked Hourglass (HG), and High Resolution (HR) networks were employed. Ways of reusing RGB channels were investigated to fill up the depth channel. Then, their performances were investigated to find out the limitations of each network structure. The results show model transfer learning by the mean way of RGB channels patching the lacking channel, can improve the average accuracies of pose key points from 1% to 20% than without transfer. 3D accuracies are 0.3% to 0.5% higher than 2D baselines. The stacked structure of the network shows better on hip and knee points than the parallel structure, although the parallel design shows much better on the residue points. As a result, the model transfer can practically fulfill boxing pose estimation from 2D to 3D.